Delayed Presentation of Patients with Acute Myocardial Infarction in Chittagong Medical College Hospital (Cardiovascular Journal, 2016)
Background: Delay between onset of symptoms and hospital presentation is a critical factor in determining the management strategy and subsequent outcome. Objective of the study was to identify predictors of late presentation in patients with acute myocardial infarction (AMI) and target interventions for those at high risk of late presentation.Methods: In our cross sectional study we prospectively analyzed a cohort of 1032 AMI patients for 1 year (August, 2014 to July, 2015). Demographic factors, clinical characteristics, perception of health and access to health care were compared between early (within 12 hours of symptom onset) and late presenters (>12 hours of symptom onset). Bivariate comparison and multivariate logistic regression were done to identify independent predictors of late presentation .Odds ratio and 95% confidence intervals were calculated directly from the estimated regression coefficient.Results: Of the total 1032 patients 385 (37.3%) were early presenters and 647 (62.7%) were late presenters. Mean time interval between onset of symptom and presentation to hospital were 6.85±8.06 hrs (range 1.5 to 12 hrs) in early and 37.88±25.13 hrs (range 13 to 120 hrs) in late presenters. Bivariate comparison found that in the late presentation group was higher age group patients and employed citizens, had ? one angina episode over past 4 weeks, was unable to use emergency medical transport, had no nearby ECG facilities and misinterpreted chest pain as peptic ulcer disease (PUD). Multivariate analysis showed older age ?65 yrs, traveling long distance ?50 miles from home residence, reporting one or more angina episode over past 4 weeks, attending PHC/clinic and misinterpreting chest pain as PUD were associated with late presentation.Conclusion: A significant majority of patients with AMI were late presenters. Misinterpreting chest pain as PUD was responsible for the delay in the majority. Reporting ?1 angina episodes over past 4 weeks was also independently associated with late presentation. Lack of emergency medical transport and traveling long distance were also significantly associated with the late presenters. Patient education, appropriate utilization of existing resources and use of tele-electrocardiography that allows transmission of ECG signal to a medical control officer may decrease late presentation and improve outcome.Cardiovasc. j. 2016; 9(1): 3-8